State Intervention on the Market for Natural Damage Insurance in Europe - Thomas von Ungern-Sternberg (Center for Economic Studies and ifo Institute (CESifo), 2003)
In this paper we briefly summarise the results of our studies of the property insurance market in 5 countries, Britain, Spain, France, Switzerland and Germany. We then draw conclusions, how the market for insurance against natural disasters (such as floods or subsidence) should be institutionally organised. Both for reasons of efficiency (lower administrative and sales costs) and to reduce the scope of risk selection, public monopolies should play an important role on this market. A further major advantage of the monopoly solution is the fact, that public insurers have a strong incentive to actively participate in prevention.
Keywords: 330